Membongkar Potensi Teknologi, Inovasi Pembelajaran Blended Learning Untuk Masa Depan Pendidikan - Zai, Novel Herman Jaya; Yahya, Zakaria; Irawan, Rayyan Wafi (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2024)
Looking at the current modern era, progress in various fields is growing rapidly, one of which is information technology. Technology was created to speed up work easily, so technology is applied in various fields such as business, office work and education. The purpose of this writing is to determine the capabilities and benefits of technology in developing education using blended learning innovations. The presence of technology in the teaching and learning process is certainly very helpful. Technology provides unlimited services and is equipped with various features that make the learning process in the classroom more attractive and interactive so that it can increase students' interest in learning.